Pressable Feldspathic Inlays in Premolars: Effect of Cementation Strategy and Mechanical Cycling on the Adhesive Bond Between Dentin and Restoration - Feitosa, Sabrina Alves [UNESP]; Corazza, Pedro Henrique [UNESP]; Cesar, Paulo Francisco; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Quintessence Publishing Co Inc, 2014)
Purpose: To evaluate the effect of the cementation strategy and mechanical cycling (MC) on the microtensile bond strength (MTBS) of feldspathic inlays cemented to premolars.Materials and Methods: Forty-eight human premolars were prepared and porcelain inlays were produced. Specimens were allocated into 3 groups, based on the cementation strategy: 1) conventional adhesive cementation (RelyX ARC, 3M ESPE): application of etch-and-rinse single bottle adhesive to dentin / ceramic surface treated with hydrofluoric acid (HF) and silane (S) / cementation with resin cement; 2) simplified cementation using a self-adhesive resin cement (RelyX U100, 3M ESPE); 3) modified simplified cementation using a self-adhesive resin cement (RelyX U100, 3M ESPE) with HF+S treatment. Half of the specimens from each group were submitted to MC (2X10(6) pulses, frequency = 4 Hz, load = 100 N). Each specimen was serially sliced for MTBS and the failures were classified. The stress distribution analysis using FEA was verified.Results: All of the bar-samples from G2 were lost during cutting of the specimens. Mechanical-cycling had no significant effect on bond strength, whereas cementation strategy significant affected MTBS results. The most common type of failure was cohesive of cement. FEA showed that stresses were concentrated mainly at the loading region going up to the root fixation.Conclusion: Porcelain inlays cemented with conventional resin cement or self-adhesive resin cement should be associated with ceramic surface treatment. FEA showed the most critical zone for failure is located in the cement region close to the marginal crest.
Keywords: microtensile bond strength; finite element analysis; inlays; mechanical cycling; feldspathic ceramic